2018
DOI: 10.3389/fnins.2018.00865
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Enhances Mitophagy and Attenuates Apoptosis After Spinal Ischemia-Reperfusion Injury

Abstract: The spinal cord is extremely vulnerable to ischemia-reperfusion (I/R) injury, and the mitochondrion is the most crucial interventional target. Rapamycin can promote autophagy and exert neuroprotective effects in several diseases of the central nervous system. However, the impact of rapamycin via modulating mitophagy and apoptosis after spinal cord ischemia-reperfusion injury remains unclear. This study was undertaken to investigate the potential role of rapamycin in modulating mitophagy and mitochondria-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 36 publications
(51 reference statements)
2
54
1
Order By: Relevance
“…Mitophagy can negatively regulate IL-1β secretion, and thus inflammatory activation, to protect against TBI-triggered immunopathology [289]. The neuroprotective effects of mitophagy have also been demonstrated in spinal cord injury, which can be induced by inhibition of miRNA-124 or autophagy inducers, such as rapamycin [292][293][294].…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…Mitophagy can negatively regulate IL-1β secretion, and thus inflammatory activation, to protect against TBI-triggered immunopathology [289]. The neuroprotective effects of mitophagy have also been demonstrated in spinal cord injury, which can be induced by inhibition of miRNA-124 or autophagy inducers, such as rapamycin [292][293][294].…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…In the early stage of spinal cord ischemiareperfusion, enhanced mitophagy can inhibit neuronal apoptosis and alleviate the symptoms of spinal cord injury. 22,[44][45][46] This study found that GIT1 played a regulatory role in mitophagy. GIT1 is vital in the development of mitochondria in the heart, but its role in neurons is unknown.…”
Section: Discussionmentioning
confidence: 58%
“…More generally, rapamycin has demonstrated beneficial effects in the context of acute CNS damage showing increased neuronal survival after spinal cord or brain injury as well as RGC rescue after optic nerve transection and ischaemia/reperfusion 36,56 . Rapamycin is well known to increase autophagy, and also upregulates mitophagy and mitochondrial fission in in vivo CNS damage models [73][74][75][76] . Supporting possible increase of mitophagy after ONC, EM pictures of RGCs after optic nerve transection show increased numbers of mitochondria in autolysosomes 6 days after the insult 36 .…”
Section: Discussionmentioning
confidence: 99%